Navigating Digital Deception: Unmasking Propaganda and Disinformation in the 2024 Elections - Irvanus Destavino; Muhammad Habibi; Muh. Reza Syamsuri (TheJournalish: Social and Government, 2023)
This research aims to understand the dynamics of disinformation and digital propaganda in the 2024 Indonesian Elections. Disinformation, often appearing as hoaxes or fake news, has emerged as a primary concern, widely disseminating through social media, threatening the integrity of the election process, and targeting specific individuals or institutions with propaganda or hate speech. The research utilizes a qualitative descriptive method. The findings from this study show that the spread of these hoaxes is exacerbated by distrust towards mainstream media, affinity towards news supporting personal views, and low levels of digital and media literacy. Initiatives like Turnbackhoax.id have played a pivotal role in assisting the community in identifying and verifying fake news. In facing the 2024 Elections, significant challenges include the dominance of first-time voters who may have low digital literacy. Consequently, there is a necessity for enhanced efforts in digital literacy education and collaboration between various parties to fight disinformation and support a fair and transparent election process. This research highlights the crucial role of Turnbackhoax.id and similar initiatives in confronting disinformation challenges leading up to the 2024 Elections.